Water resistance of bone-cements reinforced with bioceramics - OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (ELSEVIER SCIENCE BV, 2007)
The water absorption behavior of bone-cements of PMMA reinforced with 1.5 wt.%, 2.5 wt.%, and 3.5 wt.% silane-treated powders of hydroxyapatite (synthetic, or derived from bovine bones, or teeth enamel), beta-tricalcium phosphate (TCP), bioactive glass (45S5), and zirconia, was investigated. The experimental results showed that addition of calcium phosphate in the polymeric matrix favors water absorption except in the case of enamel hydroxyapatite. Water uptake is also suppressed when 45S5-bioglass or zirconia is added. The solubility is not affected by addition of hydroxyapatite or 45S5-bioglass but it increases when beta-TCP or zirconia is added. A superior behavior of bone-cements reinforced with bioglass-45S5 and enamel hydroxyapatite can be suggested. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: polymers; ceramics; composite materials; bone-cements; water resistance; MECHANICAL-PROPERTIES; HYDROXYAPATITE COATINGS; SINTERING TEMPERATURE; ZIRCONIA; PMMA; COMPOSITES; TITANIUM